Feasibility of a nursing intervention to prepare frail older patients for cardiac surgery: A mixed-methods study. (August 2015) - Ettema, Roelof; Schuurmans, Marieke J; Schutijser, Bernadette; van Baar, Mark; Kamphof, Nicole; Kalkman, Cor J
Background: Given the growing number of vulnerable, older cardiac surgery patients, the preadmission PREvention Decline in Older Cardiac Surgery patients (PREDOCS) programme was developed to reduce the incidence of postoperative complications. Before the clinical effects of such a complex multicomponent intervention can be evaluated, the feasibility needs to be determined to detect possible problems with the acceptability, compliance and delivery. Aim: The purpose of this study was to test the PREDOCS programme on its feasibility and estimate theoretical cost savings. Methods: In a mixed-methods multicentre study, the Medical Research Council (MRC) guidelines concerning testing feasibility were followed, and theoretical cost savings were calculated. We used data from interviews and the continuous data registry at three hospitals. The results were reported following the criteria for reporting the feasibility of complex interventions (CReDECI). Results: Twenty-one females and 49 males out of 114 eligible patients completed the intervention and provided full data. Patients were equally satisfied with the usual care and the PREDOCS programme (satisfaction rate respectively standard deviation (SD): 7.5 (95% confidence interval (CI): 6.4–8.7) and 7.6 (6.6–8.6)). The involved nurses were satisfied with the tools for guiding patients to reduce their risk of postoperative complications and considered the PREDOCS programme as complementary to usual care. Integrating PREDOCS into current hospital structures appeared to be difficult. Both patients and nurses indicated that the additional consult was tiresome for the patient. The PREDOCS programme will be cost-effective when postoperative complications are prevented in six to sixteen of 1000 cardiac surgery patients. Conclusions: The PREDOCS programme is acceptable for patients and nurses but should be built into the hospital's cardiac surgery pathway or applied in home care.